Entre o patrimônio e o sagrado : a Igreja São Francisco de Paula e a Venerável Irmandade do Senhor Bom Jesus dos Passos da cidade de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The São Francisco de Paula Church building, located in the city of Goiás and built in 1761, has a rich historical and cultural collection. The aim of this work is to present a survey of the material assets that have been part of the church since its construction, as well as the assets that are part of the collection of the Venerable Brotherhood of Senhor Bom Jesus dos Passos, founded in 1745, but which has had its headquarters in the São Francisco de Paula Church since 1873, and which has since become the institution responsible for managing, maintaining and conserving the church in all its aspects. The temple, in addition to housing the collection of the São Francisco de Paula Church, as well as the collection of the Venerable Brotherhood of Senhor Bom Jesus dos Passos, is of great importance to the area of Cultural Heritage Management. The aim of the inventory is to identify and document the elements present in the collection, guaranteeing the preservation of the culture and history of the Church and the Brotherhood, since the two institutions have been interconnected for almost 150 years. In addition to the research, summarized in this report, a product related to this theme was also developed with three panels, the first being an explanatory panel with historical data and a chronology of the temple's liturgical functions; the second panel, contextualizing the origin of the motets performed in that temple from the time it was installed as the headquarters of the Brotherhood of the Steps; the third panel with documentary accounts of the origin and conception of the image of the Brotherhood's patron saint, and finally a permanent photographic gallery with 93 pictures with the names and photographs of all the Brotherhood's former purveyors, the result of extensive research into the Brotherhood's documentary collection, which will also result in a handbook to be distributed to all those who visit the temple.
Between the patrimony and the sacred : the São Francisco de Paula Church and the Venerable Brotherhood of the Lord Bom Jesus dos Passos of the city of Goiás
Keywords: Patrimônio cultural, Goiás, GO; Memória; Igreja São Francisco de Paula; Irmandade; Gestão do patrimônio; Cultural heritage, Goiás, GO; Memory; São Francisco de Paula Church; Brotherhood; Heritage management; CIENCIAS HUMANAS::HISTORIA